Business Fraud dan Pola Respon Manajemen Pada Sektor Jasa Konstruksi - Nurul Sukawati Sukawati; Hafiz Rahman; Ma'ruf Ma'ruf (Fakultas Ekonomi Universitas Andalas, 2025)
This study aims to examine business fraud practices and management response patterns in the construction services sector, particularly in government projects in West Sumatra. Using a qualitative phenomenological approach, this study explores the perceptions of six construction services company leaders through in-depth interviews. The results show that fraud practices in the construction sector are influenced by external pressures, weak supervision, and individual characteristics within the organization. Management response patterns to fraud are classified into four categories: defensive, corrective, strategic, and ethical enhancement. Additionally, minimalist (pragmatic) and maximalist (idealistic) individual types play a role in shaping managerial perceptions and strategies in addressing fraud. These findings reinforce the relevance of integrating Agency Theory, Theory of Planned Behavior, and Institutional Theory in explaining the dynamics of fraud and ethical governance in the construction sector. This research provides important implications for strengthening internal control systems, fostering an integrity-driven organizational culture, and developing ethics-oriented leadership. Abstrak Penelitian ini bertujuan untuk mengkaji praktik business fraud dan pola respon manajemen pada sektor jasa konstruksi, khususnya dalam proyek-proyek pemerintah di Sumatera Barat. Dengan menggunakan pendekatan kualitatif fenomenologi, penelitian ini menggali persepsi enam pimpinan perusahaan jasa konstruksi melalui wawancara mendalam. Hasil penelitian menunjukkan bahwa praktik fraud dalam sektor konstruksi dipengaruhi oleh tekanan eksternal, lemahnya pengawasan, serta karakter individu dalam organisasi. Pola respon manajemen terhadap fraud diklasifikasikan ke dalam empat kategori: defensif, korektif, strategis, dan peningkatan etika. Selain itu, tipe individu minimalis (pragmatis) dan maksimalis (idealis) berperan dalam membentuk persepsi dan strategi manajerial dalam menghadapi kecurangan. Temuan ini memperkuat relevansi integrasi antara Agency Theory, Theory of Planned Behavior, dan Institutional Theory dalam menjelaskan dinamika fraud dan tata kelola etis di sektor konstruksi. Penelitian ini memberikan implikasi penting bagi penguatan sistem pengendalian internal, pembentukan budaya organisasi yang berintegritas, serta pengembangan kepemimpinan yang berorientasi pada etika.